Intercultural Communication Strategy Of Our Country Traditional Culture - Wei, Xing (Journal of Theory and Practice of Humanities Science, 2023)
Since the 21st century, China's economic strength has been continuously enhanced, its international status has been significantly enhanced, and its voice and influence in the world has been significantly enhanced. Meanwhile, western countries have also created the "China threat theory", which has caused many people who do not know China's national conditions and traditional culture to have a negative impression on China. the reason is closely related to the extreme lack of cross-cultural communication in China. Culture is not only the symbol and important embodiment of a country's soft power, but also the spiritual soul of a country and a nation. After 5, 000 years of development, Chinese culture has become a treasure in the history of human development. In order for China to enhance its own influence, it is particularly important to improve the attraction and appeal of Traditional Chinese culture. Therefore, it is necessary to strengthen cross-cultural communication, spread Traditional Chinese culture to all parts of the world, so that people in the world can really love, understand and accept Traditional Chinese culture, and form an influential Chinese culture.